Algorithm for the calculation of vibration inherent frequencies bending from two-shafts transmission - Grigore Jan-Cristian; Bulac Ion (MATEC Web of Conferences, 2017)
The operation of the speed shaft transmissions at or near the natural frequency of the pulses at the resonance phenomenon leads to bending, when the amplitude of the oscillations increases sharply, causing deterioration or complete destruction thereof. To avoid system resonance operation is necessary to know the most accurate values its pulsations and taking appropriate constructive measures to avoid overlapping with disturbing frequency harmonics (operating speeds).This paper presents an algorithm for calculating the pulsation and vibration modes in bending, and based on numerical simulations performed on a real two-shafts transmission and will draw conclusions drawn diagrams.